1997
DOI: 10.1093/infdis/175.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Measles with an IgM Capture EIA: The Optimal Timing of Specimen Collection after Rash Onset

Abstract: The optimal timing for collection of a single serum specimen to diagnose measles by using a monoclonal antibody-capture EIA was evaluated. Results of testing paired serum samples from 166 measles cases with at least 1 IgM-positive specimen were analyzed. Among persons whose second samples were IgM-positive, the seropositivity rate for first samples was 77% when collected within 72 h and 100% when collected 4-11 days after rash onset. Among unvaccinated persons whose first samples were IgM-positive, the rate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 14 publications
6
58
0
1
Order By: Relevance
“…This finding was also consistent with previous data, which varied from 72% to 89% by IgM IEA, for a similar period of time. We observed that the sensitivity of an assay depends on the phase of measles infection, nevertheless, the positivity reaches 100% from 4 or 5 days to 30 days after rash onset, confirming reported data (4,5,23,24).…”
Section: Resultssupporting
confidence: 90%
“…This finding was also consistent with previous data, which varied from 72% to 89% by IgM IEA, for a similar period of time. We observed that the sensitivity of an assay depends on the phase of measles infection, nevertheless, the positivity reaches 100% from 4 or 5 days to 30 days after rash onset, confirming reported data (4,5,23,24).…”
Section: Resultssupporting
confidence: 90%
“…1). For the Meddens and Denka Seiken EIAs, sensitivity increased when the sample was collected Ͼ3 days after rash onset, as has been shown for the development of the IgM response to measles virus for both vaccinated and naturally infected individuals (7,9,13). However, the sensitivity of the Behring assay was essentially the same for samples collected before and after 3 days post-rash onset.…”
mentioning
confidence: 71%
“…On the other hand, viral isolation allows us to obtain the strain for epidemiological studies. However, the sensitivity of the isolation method is low and very dependent on the time of sample collection and transport conditions; the optimal time for virus culture sampling is very early after the onset of symptoms, when specific IgM is not detected (11,14). Some reports show that genomic detection techniques, namely, PCR, notably improve the performance of the culture method (8) and should consequently be included in measles surveillance protocols.…”
mentioning
confidence: 99%